The Influence Of Emotional Intelligence On Work-Life Balance Mediated By Organizational Culture With Employee Welfare As Moderation - Supendi, Eka Tri; Maulia, Adam Hilmi; Asari, Lita; Sri W, Shelly (Talent: Journal of Economics and Business, 2024)
This study aims to explore the influence of emotional intelligence on work-life balance, by considering the role of organizational culture as a mediating variable and employee welfare as a moderation variable. Emotional intelligence, which refers to the ability to manage the emotions of oneself and others, is believed to have an influence on an individual's ability to maintain a balance between personal and professional life. However, this relationship can be mediated by an organizational culture that supports or hinders work-life balance, as well as moderated by employee well-being levels. This research is important to conduct considering the importance of maintaining a balance of life for employee welfare and organizational productivity. By understanding the role of emotional intelligence, organizational culture, and employee well-being in influencing work-life balance, organizations can develop more effective strategies and policies to support employees in achieving optimal life balance.